Technological innovation, new solutions, branding, and promotion: Twitter and technical report use in Japanese's companies. Issue 10 (26th November 2021) - Kitano, Yuta; Yamada, Tetsuo; Tan, Kim Hua
ABSTRACT: Manufacturing companies publish a variety of own data via social media platforms Twitter and also technical reports concerning the new technologies developed in-house. This study aims to analyse corporate social networking service data and technical reports to bring to light the technological innovations taking place in Japanese manufacturing companies. It uses text mining, a text data analysis method to extract useful information (from published technical reports) by dividing normal text data into words and phrases. The results show the strategic differences that exist between Twitter and technical reports in terms of bringing new information to consumers and companies.